Hybrid debt instruments: an investigation of intercompany instruments payable on demand in terms of section 8f. in partial fulfilment of the requirements for the degree master of commerce in South African taxation - De Vink, Gerard (Department of Finance and Tax, 2025)
Section 8F of the Income Tax Act, No. 58 of 1962, was introduced as an anti-avoidance provision and its recharacterisation rules came into effect in respect of amounts incurred or accrued on or after 1 April 2014. Where the ambits of this section are applied to an intercompany instrument, the interest is denied as a deduction and deemed to be a dividend in specie. As a result, the risk exposure to intergroup companies could include understatement penalties, interest and dividends tax. However, intercompany instruments that are payable on demand are excluded from the provisions of Section 8F. Therefore, this dissertation seeks to interpret the meaning of payable in demand in relation to section 8F and intercompany instruments. In order to interpret the meaning of payable on demand, this dissertation made use of a historical qualitative research approach, that is, doctrinal research. It took the form of a literature review of relevant South African and foreign jurisprudence. Non-empirical data was collected, predominantly in the form of academic articles and case law. The research indicates that an intercompany instrument that is classified as payable on demand should be regarded as repayable from the date of the agreement. No repayment demand is required in order to render the loan as due and payable. Prescription on the debt begins immediately. Having said this, the context and circumstances of the particular case, that is the intergroup companies, must be considered in determining the obligation to make repayment. Regardless of all of this, the borrower needs to be afforded the opportunity to derive some benefit from the loan transaction and enjoy the usage of the debt. Therefore, irrespective of payable on demand classifying as immediately repayable, a reasonable amount of time must be given before repayment can be expected.